Will the AIIB and the NDB Help Reform Multilateral Development Banking? - Helmut Reisen (Global Policy, 2015)
What will be the future impact of the Asian Infrastructure Investment Bank (AIIB) and the New Development Bank (NDB), two multilateral banks created in 2014 outside the established Bretton Woods system, on multilateral lending shares?
Keywords: F02; F53; 330; Global financial architecture; Multilateral Development Banking; Internationales Finanzsystem; Internationale Organisation